Técnicas alternativas para extração do óleo e aromas do maracujá - Oliveira, Ricardo Cardoso de (2012)
The worldwide consumption of tropical fruit has presented, lately, an expressive growth. Brazil is the biggest producer and consumer of passion fruit in the world. A wide use of passion fruit is done by commercial process. Juices are prepared as whole juice concentrated or frozen, The juice is frequently used to taste other fruit juice mixtures. The passion fruit seeds, industrial waste from thc squeezing process to obtain the juice, nowadays are being, most of thcm thrown away M this act represents uncountable tons of the product wasted, adding value to tilis product js of economie, scientific and technoiogic interest. The passion fruit seed is considered a ood source of ou, carbohydrates, proteins and minerals. The dryhi process of the seed is a unit operation used to remove water from the sample, thus guaranteoing the biological and chemical stability of it. Drying tests were done aecorcung to a simple factorial plan, in which the two levels of drying air temperature were 400C and 60°C, while the two levels of drying air speed were 0,6 e 0,9 m s-1. In a significance levei of 5%, the drying air temperature and the interaction between temperature and drying air speed, are the most significant factors in these drying tests. Suitability of the drying models to the data was done according to the methodology described by Bayesian Inference. No significant differences among page, modified page, Overhults and modified Overhults were found, and the Page model was chosen to describe the drying kinetics. The extraction of ou from seeds technique uses the pressing or solvent extraction. Hexane is the favorite solvent in the unit operation of extraction due to the costs and high solubility of these fatty materials. However, due to the environmental is sues and public health service, other kinds of solvents have been used in the extractions in general acetone, ethanol and isopropanol. Extractions using pressing, solvent or supercritical C02 were the techniques used in this study. All the experiments of extraction were done according to factorial plan, in which the study variables were: solvent type, extraction time and ratio seed quantity/solvent. When using the extraction via ultrasound it was noticed that for some experimental condition, especially for acetone, the extraction profits of this solvent were higher than the hexane. Hence, it can be concluded that the hexane could be. replaced by acetone in ultrasonography extractions. In the pervaporation tests were investigated the effects of temperature and concentration of the feed chain over the permeated flow of five components present in the passion fruit juice scent: isoamyl acetate, hexanal, 2-phenyl ethanoi, ethyi butyrate and linalool. The activation energies of the individual components are higher than the activation energies of the water flow, indicating that the organic component permeation, through the membrane, is more dependent on the temperature, relatively to the water permeation.